Microsatellite instability of colorectal cancer in childhood (clinical case) - S. S. Todorov (Тазовая хирургия и онкология, 2017)
Immunohistochemical study of colon adenocarcinoma in the child showed microsatellite instability MLH1, MSH2, MSH6, a high level of proliferative activity of Ki-67 and apoptosis imbalance.